Educational Impact of Research - Bispo, Marcelo de Souza; Davel, Eduardo Paes Barreto (Organizações & Sociedade, 2021)
To think about the impacts of academic research on education is to think dynamically: education affects the ways of doing research (from the point of view of formal education) and is affected by research results that are little predictable and perceived due to constant negotiations among social actors in their daily socializations in different contexts. Management education (formal, non-formal and informal) affects and is affected by conflicting views of the world, which are produced within the field of management itself and whose impact as “beneficial” is not just a matter oriented primarily by economic, instrumental and financial aspects, but also for a negotiated understanding of the world that moves towards the common good. All research must be concerned with its power to affect educational vision and practice, directly or indirectly. How can this concern become perennial and central to the practice of academic research?